Physical Activity and Lower Urinary Tract Function: Pathophysiological Mechanisms, Clinical Evidence, and Practical Implications – A Narrative Review - Jankowski , Mikołaj; Bogdan, Klaudia; Janicka, Urszula; Ciepluch, Natalia; Słomiński, Szymon; Toczek, Wiktoria; Olszówka, Magdalena; Dziugieł, Sonia (Quality in Sport, 2026)
Lower urinary tract function (LUTF) depends on complex interactions between the detrusor muscle, urethral sphincters, pelvic floor musculature, and central and peripheral neural control. Disruption of these mechanisms may lead to lower urinary tract symptoms (LUTS), including urinary incontinence, urgency, frequency, nocturia, and voiding dysfunction, which substantially impair quality of life and participation in physical activity. Physical activity is a modifiable lifestyle factor that may exert both beneficial and adverse effects on urinary tract function. Moderate, well-structured exercise enhances pelvic floor muscle strength, neuromuscular coordination, metabolic health, and autonomic regulation, whereas excessive or high-impact training may exceed pelvic floor adaptive capacity and increase susceptibility to LUTS. This narrative review synthesizes contemporary evidence (2020–2025) regarding epidemiology, pathophysiological mechanisms, sport-specific risk profiles, and clinical outcomes related to physical activity and LUTF, and discusses practical implications for screening, prevention, and clinical management in physically active populations.